A Review of Software Components Identification Methods and Quality Assessment Criteria - Ekanem, Bassey Asuquo; Agbele, Kehinde K. (European Journal of Applied Sciences, 2021)
Identification of suitable reusable software components from repositories and other sources is a key process in software reuse. Many methods for components identifying exist. However, considering the increased adoption of reuse in software projects and the need to identify appropriate components from the numerous sources based on multiple quality criteria, it becomes imperative to undertake a review of existing methods to determine their strengths and weaknesses as well as gaps in components identification. In view of the above, this research was designed to undertake a systematic review of components identification methods in software reuse. Research findings indicate that existing methods and automated tools were inadequate in handling components identification from multiple sources especially where multiple quality criteria are considered. Also, findings indicate that multi-objective optimization algorithms like non-dominated sorting genetic algorithm III (NSGA-III) are capable of addressing such multidimensional problems; therefore, greater efforts in designing and developing automated tools that are based on this technique are highly recommended. The need for adequate methods for cataloguing and categorizing components that are stored in repositories and other sources is also identified as capable of enhancing the process of components identification in software reuse.